Efficacy and Safety of Antiviral Agents in Preventing Allograft Rejection Following CMV Prophylaxis in High-Risk Kidney Transplantation: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials - Ruenroengbun, Narisa; Sapankaew, Tunlanut; Chaiyakittisopon, Kamolpat; Phoompoung, Pakpoom; Ngamprasertchai, Thundon (Frontiers in Cellular and Infection Microbiology, 2022)
Many antiviral agents have been studied in clinical trials for allograft rejection prevention following cytomegalovirus (CMV) prophylaxis in high-risk kidney transplant patients. However, data on the most effective and safest treatment are lacking. We conducted a systematic review and network meta-analysis to rank CMV prophylaxis agents for allograft rejection prevention following CMV prophylaxis in high-risk kidney transplant patients according to their efficacy and safety. We conducted searches on the MEDLINE, Embase, SCOPUS, and CENTRAL databases, as well as the reference lists of selected studies up to December 2021, for published and peer-reviewed randomized controlled trials assessing the efficacy of CMV prophylaxis agents in high-risk kidney transplant patients. Thirteen studies were independently selected by three reviewers and included post-kidney transplant patients indicated for CMV prophylaxis who had been randomized to receive prophylactic antiviral agents or standard of care. The reviewers independently extracted data from the included studies, and direct and network meta-analyses were applied to assess the study outcomes. The probability of efficacy and safety was evaluated, and the drugs were assigned a numerical ranking. We evaluated the risk of bias using the Cochrane Risk of Bias 2.0 tool. The primary outcome was an incidence of biopsy-proven acute rejection, whereas the secondary outcome was a composite of major adverse drug reactions. Each outcome referred to the definition provided in the original studies. Valganciclovir, valacyclovir, and ganciclovir were identified to significantly decrease the incidence of biopsy-proven acute rejection with pooled risk differences (RDs) of −20.53% (95% confidence interval [CI] = −36.09% to −4.98%), −19.3% (95% CI = −32.7% to −5.93%), and −10.4% (95% CI = −19.7% to −0.12%), respectively. The overall major adverse drug reaction was 5.7% without a significant difference when compared with placebo. Valganciclovir had the best combined efficacy and safety among the examined antiviral agents and was the most effective and safest antiviral agent overall for allograft rejection prevention following CMV prophylaxis. Valacyclovir was the optimal alternative antiviral agent for patients who were unable to tolerate intravenous ganciclovir or access oral valganciclovir as financial problem. However, compliance and dose-related toxicities should be closely monitored.